2010
DOI: 10.1099/ijs.0.015487-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus methylotrophicus sp. nov., a methanol-utilizing, plant-growth-promoting bacterium isolated from rice rhizosphere soil

Abstract: A Gram-positive bacterium, designated strain CBMB205 T , was isolated from the rhizosphere soil of traditionally cultivated, field-grown rice. Cells were strictly aerobic, motile, rod-shaped and formed endospores. The best growth was achieved at 30 6C and pH 7.0 in ammonium mineral salts (AMS) medium containing 600 mM methanol. A comparative 16S rRNA gene sequencebased phylogenetic analysis placed strain CBMB205 T in a clade with the species Bacillus amyloliquefaciens, Bacillus vallismortis, Bacillus subtilis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 41 publications
4
64
0
6
Order By: Relevance
“…Por otra parte, el antagonista o sus antibióticos purificados, pueden reducir la producción de deoxinivalenol por debajo del 80 % y los genes antagónicos están regulados por la presencia del patógeno (Duffy et where the highest effect was observed in B. cinerea with PRGIs of 69 and 63.5 %, respectively, A. alternata showed PGRIs 66 and 64.1 %, respectively; whereas the lowest growth reductions were registered for F. oxysporum, P. crustosum, and A. nidulans (Table 1). These results are similar to those obtained by Madhaiyan et al (2010) and Zhang et al (2012) who found a high capacity of some strains of Bacillus of the same species to inhibit the growth of several phytopathogens fungi, which was due to the production of volatile compounds and antibiotics belonging to the family of iturins and subtilins, that act on the fungi's cell wall. Also, the production of hydrophilic enzymes to break down polysaccharides, nucleic acids and lipids, which are used as an energy source, might have been involved.…”
Section: Actividad Antagónicasupporting
confidence: 80%
“…Por otra parte, el antagonista o sus antibióticos purificados, pueden reducir la producción de deoxinivalenol por debajo del 80 % y los genes antagónicos están regulados por la presencia del patógeno (Duffy et where the highest effect was observed in B. cinerea with PRGIs of 69 and 63.5 %, respectively, A. alternata showed PGRIs 66 and 64.1 %, respectively; whereas the lowest growth reductions were registered for F. oxysporum, P. crustosum, and A. nidulans (Table 1). These results are similar to those obtained by Madhaiyan et al (2010) and Zhang et al (2012) who found a high capacity of some strains of Bacillus of the same species to inhibit the growth of several phytopathogens fungi, which was due to the production of volatile compounds and antibiotics belonging to the family of iturins and subtilins, that act on the fungi's cell wall. Also, the production of hydrophilic enzymes to break down polysaccharides, nucleic acids and lipids, which are used as an energy source, might have been involved.…”
Section: Actividad Antagónicasupporting
confidence: 80%
“…The chemotaxonomic markers, including DNA G+C content, menaquinone type and the cell wall peptidoglycan, were analysed using standard protocols described previously [12,28]. The whole-cell fatty acid esters were obtained by cultivating BL9…”
Section: Dna Was Extracted From Bl9mentioning
confidence: 99%
“…Swarming motility was tested by culturing the organisms in R2A media that contained 0.4 % soft agar (w/v). In brief, the growth at different temperatures (4,15,20,25,28,37 and 42 C) was tested in R2A broth. For pH, the R2A broth was adjusted to pH 4.0-11.0 at 0.5 pH-unit intervals using acetate, phosphate and Tris buffers (used at final concentrations of 10 mM).…”
mentioning
confidence: 99%
“…The antimicrobial studies revealed that octa-O-acetylsucrose was more active against fungi and yeasts ( sumers and some are able to grow on multicarbon compounds 26 . Moreover, Bacillus methylotrophicus BM47 was reported to possess high antifungal activity against phytopathogens Fusarium oxysporum and Aspergillus flavus 27 .…”
Section: Antimicrobial Properties Of Octa-o-acetylsucrosementioning
confidence: 99%